Hello Tilly - Dunbar, Polly (Walker London, 2010)
Tilly lives in a little yellow house with her best friends. In this first book of the series, meet Tiptoe and Hector, Doodle, Pru and Tumpty as they play the trumpet, bang the drum, eat a feast and dance the Wiggle Wiggle Woo! Whump! Bump! Whoops!